A case report of right ventricular mass - Paul, GK; Sen, B; Bari, MA; Chanda, SK; Siddique, SR; Azam, MG; Khan, TA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):614-17 The abstract of this article is available on the PubMed website